Physical activity among Chinese school-aged children: National prevalence estimates from the 2016 physical activity and fitness in China—The Youth Study - Fan, X.; Cao, Z. B. (Journal of Sport and Health Science, 2017)
Purpose: This study was to present national estimates of participating in moderate-to-vigorous physical activity (MVPA) and adherence to the recommendations of 60?min/day of MVPA among Chinese school-aged children and to assess demographic differences in MVPA. Methods: Cross-sectional analyses of data from the 2016 Physical Activity and Fitness in China—The Youth Study. Participants were 90,712 primary, junior middle, and junior high school children (boy: 47%; girl: 53%), recruited from 1204 rural and urban schools across 32 administrative provinces and regions in the Mainland of China. Main outcomes were (a) average MVPA minutes per day in the previous 7 days by self-reports and (b) percentage meeting MVPA recommendations. Results: Average MVPA time was 45.4min/day, with boys having more MVPA (47.2min/day) than girls (43.7min/day) overall and across the 3 school grade categories. About 30% of participants met MVPA recommendations, with a higher percentage of boys (32%) than girls (28%) overall and across the 3 grades categories. Urban school children outperformed rural children in terms of MVPA time. Overall, boys were more likely to meet MVPA recommendations (adjusted odds ratio (aOR)=1.19, 95% confidence interval (CI): 1.16-1.22) compared with girls; children in higher grades (junior middle (aOR=0.92, 95%CI: 0.87-0.98) and junior high (aOR=0.59, 95%CI: 0.53-0.66)) were less likely to meet recommendations compared with primary school children. The odds of meeting recommendations did not differ between urban and rural children (p=0.07), but urban boys were found to be more likely to meet recommendations compared with rural boys (aOR=1.14, 95%CI: 1.06-1.19). Conclusion: Overall, the average MVPA minutes per day among Chinese school-aged children is low, and less than one-third of them meet MVPA recommendations. These results were most evident among junior middle and junior high school children and those living rural areas.